Esophageal Involvement in Wegener’s Granulomatosis: A Case Report and Review of the Literature - Glen A Fallows; Sean F Hamilton; Douglas S Taylor; S Bharati Reddy (Canadian Journal of Gastroenterology)
Wegener’s granulomatosis is characterized by a granulomatous arteritis involving the upper and lower respiratory tracts, progressive glomerulonephritis and systemic symptoms attributable to small vessel vasculitis. Although multisystemic manifestations are frequent, involvement of the gastrointestinal tract is uncommon. Cases have been reported of intestinal perforation, ulceration and hemorrhage. A patient whose initial presentation of Wegener’s granulomatosis was odynophagia secondary to esophageal vasculitis is described. Endoscopy revealed multiple punched out ulcerations in the esophagus, which resolved with standard therapy for systemic Wegener’s granulomatosis. There are only two previous reports of symptomatic esophageal vasculitis in patients with Wegener’s granulomatosis. These reports illustrate the need to consider odynophagia as a reflection of disease activity as opposed to complications of immunosuppressive therapy.